Pengenalan Kepada Generasi Alpha Manajemen Waktu ketika Bermain dan Beribadah di Bulan Ramadhan di Masjid Imaduddin Rungkut Surabaya - M Burhanuddin Abdillah (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
The Alpha generation is currently facing big challenges in balancing virtual activities and real life, where the high intensity of using devices often shifts priorities for worship, especially during the month of Ramadan. This dependence on digital screens triggers individualistic attitudes and reduces children's levels of religious participation. Therefore, this community service activity aims to increase the capacity of parents and children to implement time management and limit screen time effectively. The method used is a social marketing approach combined with participatory observation techniques, interactive visual promotions, and educational simulation games which were implemented in the Imaduddin Mosque Youth Hall, Medokan Ayu, Surabaya. The results of the activity showed a significant increase in understanding among children and parents regarding the importance of setting time limits for using devices. Generation Alpha children responded positively by enthusiastically setting their own daily priority scale between playing and worshiping without feeling forced. The implications of this activity include long-term changes to the social and spiritual dynamics of residents, the creation of a more harmonious family environment with minimal conflict related to confiscation of devices, as well as the revival of the function of mosques as centers of communal interaction for the younger generation. It is hoped that the independence of citizens in educating children will be able to build the foundation for a future generation that is digitally intelligent, mentally healthy and has a strong religious character.